2018
DOI: 10.1021/acs.iecr.7b04754
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Analysis of Diaryl Ether Decomposition under Hydrothermal Conditions

Abstract: The reactivity and decomposition pathway of models for α-O-4 and β-O-4 linkages, found within lignin, have been examined using methoxy-substituted (−OCH3) and -unsubstituted (−H) aryl groups under hydrothermal conditions. α-O-4 model compounds readily underwent conversion at comparatively mild temperatures (140–300 °C) and short reaction times (5–80 min), in contrast with the β-O-4 containing model compounds which required temperatures up to 340 °C and longer reaction times up to 240 min. Pseudo-first-order ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…However, further detailed reading can be found elsewhere. 129−133 NMR is capable of probing the nature of 1 H and 13 C nuclei in a given molecular structure, with 2D techniques, like heteronuclear single/multiple quantum coherence (HSQC/HMQC) NMR, allowing for the assessment of heteronuclear (e.g., C−H bonds), multiple-bond, or throughspace correlations that may exist in a structure. NMR techniques are able to resolve lignin structural characteristics because different relevant lignin subunitswhether they be dimers containing specific interunit linkages (e.g., phenylcoumaran, resinol, spirodienone) or monomers themselves (i.e., H, S, G derivatives)have different and identifiable chemical shifts within the NMR spectra (Supporting Information).…”
Section: Methods For Quantification Of Keymentioning
confidence: 99%
See 2 more Smart Citations
“…However, further detailed reading can be found elsewhere. 129−133 NMR is capable of probing the nature of 1 H and 13 C nuclei in a given molecular structure, with 2D techniques, like heteronuclear single/multiple quantum coherence (HSQC/HMQC) NMR, allowing for the assessment of heteronuclear (e.g., C−H bonds), multiple-bond, or throughspace correlations that may exist in a structure. NMR techniques are able to resolve lignin structural characteristics because different relevant lignin subunitswhether they be dimers containing specific interunit linkages (e.g., phenylcoumaran, resinol, spirodienone) or monomers themselves (i.e., H, S, G derivatives)have different and identifiable chemical shifts within the NMR spectra (Supporting Information).…”
Section: Methods For Quantification Of Keymentioning
confidence: 99%
“…The first major component of a microkinetic model is a well-defined lignin structure or library, which can be created from a comprehensive structural model. 3,69−71 In the case of the CPD model 65 to describe coal pyrolysis, the chemical structure of characterized coals was derived from the solid-state 13 C NMR measurements. In the CPD model, coal was described as a blend of small and large clusters.…”
Section: Microkinetic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…S18 †). Furthermore, in order to confirm the presence of the LC structure, the reported NMR data of veratrylglycol-β-guaiacyl ether (SP1) 25 were compared with the 2D-HSQC NMR spectra of the defunctionalized lignin. The comparison indicated that the β signal in the LC structure actually corresponded to H α -C β (δ H /δ C 3.99-4.29/ 73.19-74.62 ppm) in the 2D-HSQC NMR spectra (Fig.…”
Section: Dehydrogenative Decarbonylation Of Other Primary Alcohol Containing Lignin Structuresmentioning
confidence: 99%
“…1a). [24][25][26][27] The application of the B-type linkage motif was reported to avoid side reactions such as the retro-aldol reaction, which is a typical side reaction for the A-type linkage motif, especially under oxidative depolymerisation conditions. 21,[28][29][30] Thus, the use of B-type linkage motif allows for some innovative elegant approaches to valorise lignin that are not accessible for the polymeric lignin that contains A-type β-O-4 motifs.…”
Section: Introductionmentioning
confidence: 99%